ANALISIS PEMBELAJARAN BAHASA ARAB DENGAN MENGGUNAKAN KITAB DURUS AL-LUGHOH AL-‘AROBIYAH JUZ 1 DI MTs SWASTA AL-KAUTSAR AL-AKBAR - Zulheddi Zulheddi; Muhammad Iqbal (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This study aims to analyze: 1) Identity of the Durus al-Lughoh Al-'ArobiyahJuz 1 Book by Imam Zarkasyi and Imam Syubani, 2) Arabic Learning Methods Using the Duruus al-Lughoh Al-'ArobiyahJuz 1 Book at MTs Swasta Al- Kautsar Al-Akbar. This research is based on its type, this research includes field research, while the approach used is qualitative. A qualitative approach seeks to understand and interpret the meaning of an interaction event in human behavior in certain situations. Data collection techniques used in this study were observation, documentation, and interviews.The results showed that: 1) The book Durus al-Lughoh Al-'ArobiyahJuz 1 (Arabic Lesson Volume 1) was the work of Imam Zarkasyi and Imam Syubani. Imam Zarkasyi (Trimurti) is one of the founders of Pondok Modern Darussalam Gontor, while Imam Syubani is one of the teachers at Pondok Modern Darussalam Gontor. This Durus al-Lughoh Al-'ArobiyahJuz 1 book is also used as an Arabic language textbook used by students of KMI (KuliyyatulMu'allimin al-Islamiyyah) Gontor. The book Duruus al-Lughoh Al-'ArobiyahJuz 1, consists of 25 chapters described in 176 pages. 2) The process of learning Arabic using the Book of Duruus al-Lughoh Al-'ArobiyahJuz 1 at the Private MTs Al-Kautsar Al-Akbar using the muhadasah and mahfudzot methods that are most often used. This is due to the different backgrounds of students, namely some students come from Elementary School (SD), Madrasah Ibtidaiyah (MI), and Integrated Islamic Elementary School (SDIT).